World reclassification of the Gonatocerus group of genera (Hymenoptera: Mymaridae) - Huber, John T. (Zootaxa, 2015)
The 400+ nominal species of the worldwide genus Gonatocerus Nees are reclassified into 14 genera that are placed in Gonatocerini, which is defined by three putative autapomorphies. A key to the 13 extant genera of Gonatocerini is given, based on females. Five previously described genus-group taxa are recognized: Cosmocomoidea Howard stat. rev. (= ater group, of authors), Gahanopsis Ogloblin stat. rev. (= deficiens group, of authors), Gastrogonatocerus Ogloblin stat. n. (= membraciphagus group, of authors), Gonatocerus (= sulphuripes group, of authors), and Lymaenon Walker stat. rev. (= litoralis group, of authors). One new fossil genus, Archigonatocerus Huber gen. n., with two fossil species, A. balticus Huber sp. n., and A. longivena Huber sp. n. and one fossil species in Gonatocerus, G. janzeni Huber sp. n., are described, all from Baltic amber from the Eocene epoch. Eight new extant genera and 16 new extant species are described and their species keyed: Cosmocomopsis Huber gen. n., with C. flopsis Huber sp. n. and C. mopsis Huber sp. n.; Heptagonatocerus Huber gen. n., with H. madagascarensis Huber sp. n., H. magnificus Huber sp. n., H. parvus Huber sp. n., and H. pulchellus Huber sp. n.; Krateriske Huber gen. n., with K. ecuadorensis Huber sp. n., K. guianensis Huber sp. n., and K. peruensis Huber sp. n.; Octomicromeris Huber gen. n., with O. compacta Huber sp. n. and O. brevis Huber sp. n.; Pro-gonatocerus Huber gen. n., with P. albiclava Huber sp. n. and P. brunneiclava Huber sp. n; Tanyxiphium Huber gen. n., with T. breviovipositor Huber sp. n., T. longissimum Huber sp. n., and T. seychellense Huber sp. n. Yoshimotoana Huber gen. n. (= masneri group, of authors) with one included species and Zeyanus Huber, gen. n. (= asulcifrons group, of authors) with 9 included species. Keys to the species of seven genera: Archigonatocerus, Cosmocomopsis, Heptagonatocerus, Krateriske, Octomicromeris, Progonatocerus, and Tanyxiphium are provided. Information for each nominal species catalogued includes the original reference, kind, sex and depository of primary type, and subsequent references that include relevant previous generic combinations, if applicable. The type locality is given, based on original descriptions or, where necessary, subsequent publications that provide clarification on the collection locality. Two new synonyms are proposed: Gonatocerus similis Gupta & Poorani, 2008, syn. n. under G. bialbifuniculatus Subba Rao, 1989; and Gonatocerus hispaniolus Triapitsyn & Huber, 2010, syn. n. under G. masneri Yoshimoto, 1990. Among the species, 245 new combinations are proposed: 82 in Cosmocomoidea, 1 in Cosmocomopsis, 4 in Gahanopsis, 8 in Gastrogonatocerus, 3 in Gonatocerus, 135 in Lymaenon, 2 in Tanyxiphium, 1 in Yoshimotoana, and 9 in Zeyanus. Revived combinations are proposed for Twelve species: 1 in Cosmocomoidea, 1 in Gahanopsis, 2 in Gonatocerus, and 8 in Lymaenon. The 410 nominal species group names are catalogued under their currently accepted genus and also listed alphabetically in an appendix. A tentative generic phylogeny is proposed.